Fine mapping of Pm71, a novel powdery mildew resistance gene from emmer wheat - Jiadong Zhang; Hong Yang; Guohao Han; Hongxing Xu; Ruishan Liu; Ningning Yu; Ran Han; Yaoxue Li; Jiatong Li; Yintao Dai; Cheng Liu; Yuli Jin; et al. (Crop Journal)
Powdery mildew negatively impacts wheat yield and quality. Emmer wheat (Triticum dicoccum), an ancestral species of common wheat, is a gene donor for wheat improvement. Cultivated emmer accession H1-707 exhibited all-stage resistance to powdery mildew over consecutive years. Genetic analysis of H1-707 at the seedling stage revealed a dominant monogenic inheritance pattern, and the underlying gene was designated Pm71. By employing bulked segregant exome sequencing (BSE-Seq) and using 2000 F2:3 families, Pm71 was fine mapped to a 336-kb interval on chromosome arm 6AS by referencing to the durum cv. Svevo RefSeq 1.0. Collinearity analysis revealed high homology in the candidate interval between Svevo and six Triticum species. Among six high-confidence genes annotated within this interval, TRITD6Av1G005050 encoding a GDSL esterase/lipase was identified as a key candidate for Pm71.